Gross, Histologic, and Computed Tomographic Anatomy of the Lacrimal System of Snakes - Souza, Nicole M. (Vet Ophthalmol, 2014)
OBJECTIVE: To describe the lacrimal system of snakes using contrast micro-computed tomography (micro-CT) with 3-dimensional reconstruction, fluorescein passage (“Jones”) testing, histology, and gross dissection. ANIMALS STUDIED: One Royal Python and 19 snake cadavers representing 10 species. PROCEDURES: Direct observation following injection of fluorescein into the subspectacular space, micro-CT following injection of 3 contrast agents into the subspectacular space, gross dissection following injection of latex into the subspectacular space, and histopathology. RESULTS: Injection of fluorescein confirmed patency but not course of the lacrimal duct. Barium enabled clear visualization of the lacrimal duct whereas two iodinated contrast agents proved inadequate. Collectively, micro-CT, anatomic dissections, and histology suggest tears are produced by a single, large, serous, retrobulbar gland, released into the subspectacular space via several ductules, and drained through a single punctum originating in the ventronasal subspectacular space and the lacrimal duct taking one of 3 routes of variable tortuosity before opening into the oral cavity in close association with the opening of the duct of the vomeronasal organ. CONCLUSIONS: The ophidian lacrimal duct has a generally tortuous course and the details of its anatomy is species variable. The tortuous course of the duct likely predisposes snakes to duct occlusion and must be considered when planning medical and surgical interventions in snakes with pseudobuphthalmos and subspectacular abscessation.